A Protocol for a Comprehensive Monitoring and Evaluation Framework With a Compendium of Tools to Assess Quality of Project ECHO (Extension for Community Healthcare Outcomes) Implementation Using Mixed Methods, Developmental Evaluation Design - Ghosh, Smita; Roth, Brenna M.; Massawe, Irene; Mtete, Emmanuel; Lusekelo, Jacob; Pinsker, Eve; Seweryn, Steven; Moonan, Patrick K.; Struminger, Bruce B. (Frontiers in Public Health, 2021)
Introduction: The United States Centers for Disease Control and Prevention (CDC), through U.S. President's Emergency Plan for AIDS Relief (PEPFAR), supports a third of all people receiving HIV care globally. CDC works with local partners to improve methods to find, treat, and prevent HIV and tuberculosis. However, a shortage of trained medical professionals has impeded efforts to control the HIV epidemic in Sub-Saharan Africa and Asia. The Project Extension for Community Healthcare Outcomes (ECHOTM) model expands capacity to manage complex diseases, share knowledge, disseminate best practices, and build communities of practice. This manuscript describes a practical protocol for an evaluation framework and toolkit to assess ECHO implementation. Methods and Analysis: This mixed methods, developmental evaluation design uses an appreciative inquiry approach, and includes a survey, focus group discussion, semi-structured key informant interviews, and readiness assessments. In addition, ECHO session content will be objectively reviewed for accuracy, content validity, delivery, appropriateness, and consistency with current guidelines. Finally, we offer a mechanism to triangulate data sources to assess acceptability and feasibility of the evaluation framework and compendium of monitoring and evaluation tools. Expected impact of the study on public health: This protocol offers a unique approach to engage diverse group of stakeholders using an appreciative inquiry process to co-create a comprehensive evaluation framework and a compendium of assessment tools. This evaluation framework utilizes mixed methods (quantitative and qualitative data collection tools), was pilot tested in Tanzania, and has the potential for contextualized use in other countries who plan to evaluate their Project ECHO implementation.